From the Battlefield of Books: Essays Celebrating 50 Years of the Taylor-Schechter Genizah Research Unit: Cambridge Genizah Studies Series, Volume 16 - Connolly, Magdalen M.; Outhwaite, Ben; Posegay, Nick (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025, 2025)
This collection of essays celebrates 50 years since the founding of the Taylor-Schechter Genizah Research Unit at Cambridge University Library. Three generations of scholars contributed their research and memories from their time at the GRU, stretching back to 1974. Their work comprises 18 articles on medieval Jewish History, Hebrew and Arabic manuscripts, archival history, and the story of the Cairo Genizah collections at the University of Cambridge. Together, they demonstrate the achievements of GRU alumni in advancing the field of Genizah Studies for more than five decades. See Less